The Green Investment Effect on the Regulation of Idle Well Management Cooperation Contract Schemes - Sang Ayu Putu Rahayu; Rahayu Fery Anitasari; Dina Silvia Puteri; Nathanael Bayu Ajie Pratomo; Anak Agung Ayu Diah Setyawati (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
This research delves into legal issues surrounding the impact of green investment on cooperation contracts managing idle wells in Indonesia, Malaysia, and Equatorial Guinea. In alignment with green investment principles, the Indonesian Government has implemented various schemes to enhance the effectiveness of exploration and exploitation activities in the oil and gas sector. Presently, efforts to boost oil and gas production involve reactivating idle wells, yet there is a regulatory gap concerning the transfer of this work to cooperation contract contractors. To address this, the study compares how Malaysia and countries in the Guinea Region, adopting green investment practices, manage idle wells. Employing a socio-legal methodology, the research draws on field research, legal sources, articles, journals, and related news. The findings highlight the crucial role of acknowledging the ongoing significance of oil and gas while recognizing the imperative to transition sustainably, exemplified by Indonesia's commitment and the potential application of the Production Sharing Contract (PSC) scheme in shaping the future of non-fossil energy sources in the realm of upstream oil and gas investment.